An innovative uncertainty management framework to support contracting for product-service availability. Issue 5 (14th October 2014) - Ahmet Erkoyuncu, John; Roy, Rajkumar; Shehab, Essam; Kutsch, Elmar
Abstract : Purpose: – In the light of challenges experienced in cost estimation at the bidding stage of complex engineering services in the defence industry (e.g. contracting for availability), the purpose of this paper is to present a framework to manage the influence of uncertainty on cost estimates. Design/methodology/approach: – The research applied the Soft Systems Methodology and benefitted from interaction with four major organisations in the defence industry through document sharing, semi-structured interviews, workshops, and case studies. Findings: – The framework is composed of seven stages to plan, identify, prioritise, classify, and manage cost uncertainties. Through the validation of three case studies some of the key benefits of the framework were realised in project planning, uncertainty visualisation, and capability management. Research limitations/implications: – The research has been applied in the defence sector in the UK and focuses on the bidding stage. Further research needs to be applied to confirm that the findings are applicable across industries and across the life cycle. Originality/value: – The paper builds on the theory behind risk and uncertainty management and proposes an innovative framework that avoids the assumption of "perfect" knowledge by raising questions about the validity of the input data.